The Influence of Internship Experience, Creative Thinking, and Critical Thinking on Work Readiness Mediated by Professional Attitude of Vocational High School Students in Batang Hari - Herry Sofyandy Pranata; Firman, Firman; Rosmiati, Rosmiati (Tinta Emas Institute, 2025)
This research aims to examine the influence of PKL experience, critical thinking, creative thinking ability on job readiness mediated by the professional attitude of students at SMKN Batang Hari. This research uses a quantitative survey approach. The population in this study was 287 students. Sampling using random sampling technique. Research data was tested using Structural Equation Modeling (SEM) with the help of the SmartPLS application (v.3.2.9). The results of the research show that there is a significant positive direct influence on the influence of PKL experience, critical thinking, creative thinking ability on job readiness. And then there is an indirect influence on the influence of PKL experience, critical thinking, creative thinking ability on job readiness, mediated by students' professional attitudes. The novelty in this research is the introduction of the Astin I-E-O (Input-Environment-Output) theory integration model with the Theory of Planned Behavior (TPB) which can increase the Work Readiness of vocational school students through the influence variables of PKL experience, ability to think creatively, think critically, and professional attitude. High levels of students have an impact on increasing better work readiness. This research can be a basis for making policies or programs to increase the Work Readiness of vocational school students. Apart from that, this research also aims to deepen understanding of the factors that influence vocational school students' work readiness and provide suggestions for developing more effective policies and programs in vocational high schools.